(3EjVGM GdebGUO daQGFO GdahGFO GdHgjIs - (3jMji CMeO GdcGTis; (3ceGd GdOjf MSf GdaGQSjs ((3YHO GdQMef Hf eMehO Hf CMeO GdYWGQi s)
(3ChdgG (B:s
(3CeG HYO aEfg deG hab ddYHO jMji CMeO GdcGTi GdPi jQLhG ai cQe QHg GdYdhe GdYbdjI hGdfbdjI hMbGFb GdeYGQa GdEdgjI s
(3BNQgG (B:s
(3hai NGWQi Cf CcJH ai gPG GdHGH hGddg GYde HGdUhGH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdQjGVjGJs